Short-term fluctuations in personal black carbon exposure are associated with rapid changes in carotid arterial stiffening. (March 2016) - Provost, Eline B.; Louwies, Tijs; Cox, Bianca; op 't Roodt, Jos; Solmi, Francesca; Dons, Evi; Int Panis, Luc; De Boever, Patrick; Nawrot, Tim S.
Abstract: Background: Vascular changes may underpin the association between airborne black carbon (BC) and cardiovascular events. Accurate assessment of personal exposure is a major challenge in epidemiological research. BC concentrations are strongly related to time–activity patterns, which is particularly relevant when investigating short-term effects. We investigated associations between arterial stiffness and personal short-term BC exposure. Methods: This panel study included 54 healthy adults (92% women, mean age 40.7 years). BC exposure was monitored individually with a micro-aethalometer during one workweek. Functional and structural properties of the carotid artery were examined ultrasonographically on two separate days. The effect of different short-term personal BC exposure windows (1, 2, 4, 6, 8, 24 and 48 h before the ultrasound examination) on carotid artery stiffness was estimated using mixed models while adjusting for other known correlates of arterial stiffness. Results: Median personal BC exposures within the same day ranged from 599.8 to 728.9 ng/m 3 and were associated with carotid arterial stiffness measures. Young's elastic modulus and pulse wave velocity, both measures of stiffness, were positively associated with BC exposure, while the distensibility and compliance coefficient, measures of elasticity, were negatively associated with BC exposure. The strongest associations were observed with BC exposure 8 h before the clinical examination. For each 100 ng/m 3 increase in exposure within this time window, Young's elastic modulus increased by 2.38% (95% CI: 0.81 to 3.97; P  = 0.0033), while the distensibility coefficient decreased by 2.27% (95% CI: − 3.62 to − 0.92; P  = 0.0008). Conclusions: Short-term elevations in personal BC exposure, even within hours, are associated with increased arterial stiffness. This response may reflect a pathway by which air pollution triggers cardiovascular events. Highlights: Investigates the influence of short-term fluctuations in black carbon exposure on arterial stiffening Exposure assessment is based on personal measurements of black carbon Repeated clinical examination of carotid artery stiffness measures Elevations in same day exposure to black carbon, even within hours, are associated with increased arterial stiffness